Analisis Preferensi Konsumen terhadap Teh Kulit Mangga Hasil Perbedaan Metode Produksi dan Penyajian: Analysis of Consumer Preferences for Mango Skin Tea Based on Differences in Production and Serving Methods - Yudiastuti, Silvia Oktavia Nur; Rohmah, Febri Safinatur; Halim , Abdul; Handayani, Wiwik (Jurnal Ilmiah Inovasi, 2026)
Mango (Mangifera indica L) is one of the fruits that is widely produced in Indonesia, but the utilization of its peel has not been maximized. Mango peel is generally discarded as waste from mango fruit. Mango peel is known to contain bioactive compounds such as high phenolic compounds that can act as antioxidants. Mango peel can be developed into tea to increase its added value and minimize mango food waste. This study aims to determine the processing of mango peel tea using the blanching and wilting methods as the initial stages of processing and to evaluate the level of consumer acceptance of mango peel tea. This study was conducted using a Completely Randomized Design (CRD) with two factors in serving tea, namely tea concentration (2%, 4% and 6%) and brewing time (3, 5, and 7 minutes). The parameters observed were hedonic organoleptic tests including taste, aftertaste, aroma, and color involving 25 panelists. The test results showed that the production method, concentration and brewing time affected the level of panelist preference. The best formulation obtained was mango tea with a wilting process, with a tea concentration of 2% and a brewing time of 5 minutes.